Patterns of peri-gestational weight change among women living with HIV in Nigeria receiving dolutegravir compared to alternative antiretroviral regimens: a retrospective cohort study - Ammar Al Naimi; Charlotte Chang; Holly Rawizza; Oluwaseun Olaifa; Olabanjo Ogunsola; Prosper Okonkwo; Phyllis Kanki (AIDS Research and Therapy)
Abstract Background Weight change for women living with HIV (WLWH) who receive dolutegravir (DTG) is understudied around pregnancy. The aim of this study was to investigate the direction and magnitude of weight change among WLWH pre-, during, and post-gestation based on DTG exposure history. Methods This retrospective cohort study evaluated adult pregnant WLWH receiving antenatal care between 2016 and 2022 at two clinics in Nigeria and followed them over three 9-month periods (pregestational, antenatal, and postgestational). Patients were stratified into three DTG exposure groups for each follow-up period: non-DTG, DTG-switch, and DTG. Three mixed effects models with random intercepts and slopes were utilized to assess the association between DTG and weight. Sensitivity analysis was conducted using binomial DTG exposure with starting time. Results The study included 2386 women, 851 (35.7%) of whom used DTG at some point. Average maternal weight was 63.8 ± 12.7 kg, 67.0 ± 13.1 kg, and 64.5 ± 12.7 kg during the pregestational, antenatal, and postgestational period. The weight difference in kg for DTG and DTG-switch compared to other ARTs were 0.06 (-1.66, 1.79) and -2.11 (-5.33, 1.11) pregestational, -0.613 (-2.14, 0.92) and 1.21 (-0.80, 3.21) antepartum, and 2.64 (0.37, 4.91) and 0.89 (-1.40, 3.18) postgestational. The antenatal slope (β) for DTG exposure and initiation time was 0.01 (0.001, 0.02) kg/day. Conclusions DTG therapy is associated with more rapid weight gain during pregnancy without significantly affecting the total weight gained. Moreover, retained weight postgestation is higher in women on DTG. Therefore, they could face higher future metabolic and cardiovascular risks.